Meaning - Schiffer, Stephen (Oxford Clarendon Press, 1988)
What is it for marks or sounds to have meaning, and what is it for someone to mean something in producing them? Answering these and related questions, Schiffer explores communication, speech acts, convention, and the meaning of linguistic items in this reissue of a seminal work on the foundations of meaning. A new introduction takes account of recent developments and places his theory in a broader context.